Análisis del riesgo financiero y su influencia en la toma de decisiones para el microempresario del cantón Buena Fe, año 2014 - Chavarría Menéndez, Betty Johanna (2015)
In the city Buena Fé Los Rios province, was investigated on "Financial Risk Analysis and its Influence on Decision Making for buenafesino businessman". A microenterprise is a "natural or legal person who operates in the market producing and / or marketing goods or services for own risk, with a fixed or mobile shop that has a level of annual gross sales to 476.2 urban minimum wage. To reach the stated objective methodology Type field descriptive, explanatory and exploratory where he took into account 30 micro level was used. The research design was through deductive and inductive methods which allowed the investigating organized and methodical character obtain an effective result of the inquiry conducted. It is also structured as follows in Chapter 1 is all on the conceptual framework of the research, in chapter 2 theoretical framework where the whole theory of different authors with their appointments and years is found, chapter 3, the methodology, chapter 4 results and discussion with the analysis and interpretation of each of the surveys to micro - entrepreneurs and finally chapter 5 concludes with their recommendations. These results argue that micro is currently not conducting a risk analysis timely decision making so it has caused a low income, limited competitiveness and making wrong decisions. The advantages of analyzing the financial risk is that visualizes existing problems in the microenterprise as a timely diagnosis decision making can prevent failure and prevent the bankruptcy of the same. From this perspective, this work becomes a contribution to the microenterprise sector through which the main beneficiaries will be the entrepreneurs since by which these will have both an economic and competitive business, cantonal level growth, provincial and why not nationally.